Measures of criminal justice response to prohibitions in the field of traffic safety and vehicle operation: some aspects of regulatory certainty and practice of use - Iashchenko, Andrii (Archives of Criminology and Forensic Sciences, 2020)
The article is devoted to the research of measures of criminal justice response to prohibitions in the field of traffic safety and vehicle operation. It is noted that the primary role in state response to violation of criminal justice prohibitions in the field of traffic safety and vehicle operation is given to punishment, but no less important role is paid to other alternative to prohibition measures of criminal justice nature based on the concussion (special confiscation) or the encouragement (exemption from criminal responsibility or serving a sentence). It is concluded that the normative regulations of threats of application of certain punitive measures of criminal justice nature in sanctions of the articles of this section of the Special part in which the legislator defines the threat of application of various types of punishment for committing the crimes stipulated in crimes’ dispositions, needs specification from the point of view of the system interconnection, along with the provisions of the General Part of the Criminal Code of Ukraine, whereas the practice of application of special confiscation its further distribution and development, considering the proposed recommendations of its delimitation with the so called criminal procedural confiscation as means of criminal procedural concussion. In particular, it is noted that such clarification may be implemented either by enforcing additional penalties specified in the sanctions of Part 1, 2, 3 of Article 286, part 1 of Article 287 of the Criminal Code of Ukraine, to the common list of types of punishments, with their separate meaningful definition in the corresponding articles of the section X of the General part of the Criminal Code of Ukraine, or by covering normative definition in sanctions of the specified articles of section XI of the Special part of threats of application of such additional types of punishments according to the existing parts of the Criminal Code of Ukraine. In this regard the sanctions of Article 286 and 287 of the Criminal Code of Ukraine propose to make appropriate changes. As for the practice of applying special confiscation for committing crimes in the field of traffic safety and vehicle operation, it is recommended that the question of its implementation should be based on the fact that the subject of special confiscation may be defined in paragraph 1 of Part 1 of Art. 96-2 of the Criminal Code - items 6, 6-1 part 9 of Art. 100 of the Criminal Procedure Code, paragraph 2, part 1 of Art. 96-2 of the Criminal Code - item 2 part 9 of Art. 100 of the CPC, paragraph 3, part 1 of Art. 96-2 of the Criminal Code - item 5 part 9 of Art. 100 of the CPC, paragraph 4, part 1 of Art. 96-2 of the Criminal Code - item 1 part 9 of Art. 100 of the CPC items of the material world that possess a certain property value, and are usually considered as physical evidence in criminal proceedings initiated on the fact of committing certain crimes in the field of traffic safety and vehicle operation.